THE SUSTAINABILITY OF BANK MAJALENGKA IN 2018-2023: ANALYSIS THE INFLUENCE OF NET INTEREST MARGIN (NIM) AND LOAN TO DEPOSIT RATIO (LDR) ON THE RATE OF RETURN ON ASSET (ROA) - Yelsha Dwi Pasca; Tia Aprilia Susnita (STIESA Press, 2025)
Banks are financial institutions that are required to produce profitability in order to carry out their functions and roles. Profitability assessment uses Return on Assets (ROA). The higher the ROA of a bank, the greater the bank's ability to generate profits. Currently Net Interest Margin (NIM) still gets the main attention of banks in Indonesia considering that NIM is directly related to the bank's ability to manage productive assets which are still dominant in the credit business. LDR is a ratio to measure the composition of the amount of credit given compared to the amount of public funds and own capital used. The increase in this ratio shows the bank's effectiveness in channeling funds that have been collected in the form of credit so that the bank has the opportunity to achieve higher interest income to increase profitability. The purpose of this research is to find out and analyze how much influence NIM and LDR have on ROA at Bank Majalengka. The data used in this research is secondary data in the form of the annual financial report of Bank Majalengka for the period 2018-2023. Data analysis techniques in this research include hypothesis testing consisting of multiple regression coefficient tests, correlation coefficient tests, R2 model tests (coefficient of determination), t test (partial test) and F test (simultaneous). Based on the research results, it shows that NIM and LDR jointly influence the ROA of Bank Majalengka. The greater the ROA ratio value, the better the level of banking business. Keywords: NIM, LDR and ROA.